The life of Saint Norbert: founder of the Order of Prémontré : Vita Norberti B - Antry, Theodore James (The Norbertine Canonesses of the Bethlehem Priory of St. Joseph, 2021)
Keywords: 👤 norbert of xanten

The Canons Regular: St Norbert and the Premonstratensians - Thonippara, Francis (Vinayasādhana: Dharmaram Journal of Psycho-Spiritual Formation, 2021)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Man on Fire. The Life and Spirit of Norbert of Xanten - Kunkel, Thomas (Center for Norbertine Studies, 2019)
Keywords: 👤 norbert of xanten

The Translation of St. Norbert’s Remains to Prague in 1627: True account of a letter sent by St. Michael’s of Antwerp to the Canons Regular of the Monastery of Saint Norbert of Madrid - Sands, Rosemary (Communicator: The English Speaking Circary of the Order of Prémontré, 2018)
Keywords: 👤 norbert of xanten

St. Norbert and His Order (Mediatrix Press, 2015)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

A Norbert for England: Holy Trinity and the Invention of Robert of Knaresborough - Easterling, Joshua (Journal of Medieval Monastic Studies, 2013)
This essay considers the relationship between two monastic vitae and their historical subjects. The prose vita of the English hermit Robert of Knaresborough that is extant in London, British Library, MS Egerton 3143 contains a number of passages borrowed from the Vita B of Norbert of Xanten, the founder of Premontre. These two otherwise unaffiliated figures of religious reform are connected through Robert’s biographer, most likely a brother of the late-established Trinitarian Order, who extracted key details from Norbert’s vita to shape Robert in the founder’s image. In Egerton’s prose vita, Robert is ultimately made to serve as a legitimate origin for, and as a founder of, the Trinitarian Order at Knaresborough.
Keywords: 👤 norbert of xanten

Norbert and early Norbertine spirituality - Antry, Theodore J.; Neel, Carol (Classics of Western Spirituality, 2007)
Keywords: 👤 norbert of xanten

Norbert of Xanten: Preaching to the people, converting the clergy - Van Engen, John (Reclaiming Our Norbertine Heritage: Lectures Presented in Honor of the 100th Anniversary of the Norbertine Presence in the Green Bay Diocese, 1995)
Keywords: 👤 norbert of xanten

On the date of John Capgrave's Life of St. Norbert - Lucas, Peter J. (The Library: The Transactions of the Bibliographical Society, 1981)
Keywords: 👤 john capgrave; 👤 norbert of xanten

The life of St. Norbert by John Capgrave, O.E.S.A.: 1393 - 1464 - Capgrave, John (Studies and texts, 1977)
Keywords: 👤 john capgrave; 👤 norbert of xanten

John Capgrave's first English composition, "The Life of St. Norbert" - Fredeman, Jane Cowan (Bulletin of the John Rylands Library, 1974)
Keywords: 👤 john capgrave; 👤 norbert of xanten

Capgrave's Life of St. Norbert: direction, dialect and spelling - Smetana, Cyril Lawrence; Colledge, Edmund (Mediaeval Studies, 1972)
Keywords: 👤 john capgrave; 👤 norbert of xanten

History of Saint Norbert, founder of the Norbertine (Premonstratensian) Order, Apostle of the Blessed Sacrament, Archbishop of Magdeburg - Kirkfleet, Cornelius J (B. Herder, 1916)
Keywords: 👤 norbert of xanten

The life of S. Norbert, founder of the Order of Prémontré, Archbishop of Magdeburg - Geudens, Martin (R. Washbourne, 1886)
Keywords: 👤 norbert of xanten